The study of urban landscape visual sensitivity assessments: a case study in the Zhongshan District of Dalian. Issue 2 (3rd July 2018) - Wang, Fangxiong; Qu, Xinyu
ABSTRACT: This paper uses slope, distance, visual probability and remarkableness as evaluation indices to study urban landscape visual sensitivity in the Zhongshan District of Dalian. The results show that areas of high sensitivity account for 14.12% of the total area, these areas should be protected. Moderate sensitivity areas occupy 2.66%, urban landscape transformation should be carried out properly. Low-sensitivity areas accounted for only 0.74%, the utilization of vegetation and the construction of public facilities can be carried out in these areas. Areas classified as insensitive account for 82.48%, this is a potential zone where the urban landscape can be developed.